A novel auxiliary unit based high gain DC-DC converter for solar PV system with MPPT control - Asapu Siva; Vanitha Rajendran (Institute of Advanced Engineering and Science, 2022)
Solar photovoltaic (PV) system becomes popular to generate the electricity in Asian region and helps to reduce the burden to utility. The power converter plays crucial role to interconnect with DC- grid. Traditional type power DC-DC converter can able to extract the maximum power from solar PV. However, most of the applications, it often fails to meet the voltage level of the DC bus and additional converter is required to boosting p the DC voltage. In order to overcome this drawback, this paper proposes a novel DC-DC converter to extract the maximum power from solar PV and helps to enhance the voltage level to meet the DC-bus. The PV and IV characteristics of practical solar PV cell and mathematical modelling have been done and implemented the same to proposed high gain converter. The maximum power point tracking (MPPT) algorithm and operation details are addressed and the detailed operation waveform of proposed high voltage gain DC-DC converter with mathematical evident is reported in this paper. The simulation study was carried out in the PSCAD/EMDTC software. From the measured results, it is investigated in further to validate the MPPT operation, gain values achievement and performance analysis of proposed converter. The corresponding explanations and results are presented in this article.